Respuesta :
To solve this you first expand the brackets.
4x^2 - 20x + 25 = 49
Then make it equal 0.
4x^2 - 20x - 24 = 0
Now solve the quardratic.
x^2 - 5x - 6 = 0
(x - 6)(x + 1) = 0
x = 6 or x = -1
4x^2 - 20x + 25 = 49
Then make it equal 0.
4x^2 - 20x - 24 = 0
Now solve the quardratic.
x^2 - 5x - 6 = 0
(x - 6)(x + 1) = 0
x = 6 or x = -1
First, simplify the equation.
4x2−20x+25=49
Step 2: Subtract 49 from both sides.
4x2−20x+25=49 - 49
4x2−20x−24 =0
Step 3: Factor left side of equation.
4(x+1)(x−6)=0
Step 4: Set factors equal to 0.
x+1=0 or x−6=0
Your answers:
x=−1 or x=6
4x2−20x+25=49
Step 2: Subtract 49 from both sides.
4x2−20x+25=49 - 49
4x2−20x−24 =0
Step 3: Factor left side of equation.
4(x+1)(x−6)=0
Step 4: Set factors equal to 0.
x+1=0 or x−6=0
Your answers:
x=−1 or x=6